Beginning Japanese - Jorden, Eleanor Harz (Charles E. Tuttle Company, 1963)
Japanese is the language of approximately 125 million people. This course, developed by Eleanor Harz Jorden of Cornell University, is concerned only with spoken Japanese in the "standard" dialect of educated inhabitants of Tokyo. Learning to speak the languageat normal speed is emphasized next since the aim of the course is to teach the learner to understand and speak the everyday language just as it is spoken by the Japanese